ANALISIS TINGKAT KEPERCAYAAN, KEMUDAHAN PENGGUNAAN DAN BRAND EQUITY TERHADAP MINAT PENGGUNAAN M-BANKING - Putu, Purnama Dewi; Cecilia Da Conceicao Lemos (Media Bina Ilmiah, 2024)
Timor Leste people who live in the city of Denpasar in their daily activities use m-banking to transfer money to their country. The use of overseas transfer services is something that the people of Timor Leste pay attention to to ensure that the money sent can be sent on time to their country of origin. using m-banking so that the people of Timor Leste need a bank in Indonesia that is capable of dealing with the risks that occur in transferring money. This study aims to determine the effect of the level of trust, convenience, brand equity on intention to use. The sample in this study were 100 people. Data analysis techniques using validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination test, F test and t test. From the results of the study, it was obtained that the level of trust had a significant positive effect on intention to use, ease of use had a significant positive effect on intention to use and brand equity had a significant positive effect on intention to use. The magnitude of the influence of the independent variables on interest in use is 60.2%. The advice that can be given by researchers is that BNI Bank should periodically update the m-banking application so that later it is able to give trust to customers, ease of use and can provide high security in transactions